(3NdGUI GdCacGQ aj HjGf RHOI GdCSQGQ ef TQM GdeTcd ef dH GddHGHs - (3YHO Gddg Hf eMeO Hf CMeO , GdfbQg cGQs; (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj GdTjQGRj, CHh SYjO CHh GdNjQ fGUQ GdOjf GdHjVGhj,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi QaY bOQ GdYdeGA hHYO aEf GdYdhe GdJi JTYHJ afhfgG dGJNai aNGeJgG hdG jfcQ LdGdJgG hYdi GdfMh ef HjfgG CMSfgG TCfkG hbO Cda GdfGS ajgG cJHkG dGjMUi YOgG dcf cJGH dH GdCdHGH s
(3BNQgG (B:s
(3hbGd SeYfG ef jhKb Hg jbhd (B: (3gPG Safi (B" (3jQjO gPG Sja MGO Ch eGVi Ch fMhgG ef GdUaGJ afSi heO eJPcQkG EPG de jQO Cf jbWY GddaX hGddg CYde HGdUhGH gPG BNQ eG CQOfG EjQGOg ai GdcJGH ef cJGH dH GdCdHGH Je GdcJGH HYhf Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs